Do self-reported data reflect the real burden of lifetime exposure to sexual violence among females aged 13–24 years in Malawi?. (August 2016) - Fan, Amy Z.; Kress, Howard; Gupta, Sundeep; Wadonda-Kabondo, Nellie; Shawa, Mary; Mercy, James
Abstract: Background: Under most circumstances, the lifetime experience of sexual violence (SV) among girls and young women would likely increase with age. However, the empirical data from a retrospective study may not necessarily conform to this belief. Methods: Data from a nationally representative sample of females aged 13–24 years in Malawi in 2013 ( n = 1029) were analyzed. SV was defined as unwanted touching or attempted, pressured, or physically forced sex. The distribution of four types of SV among victims was compared between younger (13–18 years) and older (19–24 years) age groups. The strength of association between SV exposure and health outcomes was examined by age group. Results: The risk of experiencing SV during their lifetime was three times greater for younger than that for older age females (Hazard ratio = 3.32). Among females who had experienced SV, older age females were more likely to report forced or pressured sex (41.2%) as their initial SV experience than younger age females (17.8%). The strength of association between the SV exposure and health outcomes did not differ by age group. Conclusions: The self-report lifetime and childhood victimization to sexual violence may not necessarily higher among older than that among younger females. The current risk of exposure to sexual violence seems to influence the recall of lifetime and childhood victimization to a great extent. In order to make the field aware of this phenomenon, prevalence estimates from all three time frames (lifetime, childhood, and during the past 12 months) should be reported separately by age group.